Kamisama kiss. Vol. 14 - Suzuki, Julietta (Viz Media, LCC, 2014)
"Himemiko and Kotaro's happy ending has triggered some confusing flashbacks for Tomoe, and his memories are affecting more than just his mood. The shrine has started to collapse because Tomoe isn't strong enough to maintain it, and things have gotten so bad that the kami Mikage returns. He explains to Nanami that Tomoe is dying from a 500-year-old curse, and there's nothing she can do to save him!"--Back cover.